Rat Taro Extract (Typhonium flagelliforme (Lodd.)) as A Biofungicide Against the Cause of Leaf Fall (Pestalotiopsis sp.) on Rubber Plants (Hevea brasiliensis) - Noer, Zulheri; Manik, Prendy Jonringga; Sihotang, Saipul (Postgraduate, University of Mataram, 2023)
Typhonium flagelliforme or known as rat taro is a herbaceous plant that belongs to the taro tribe. The results of the phytochemical analysis of the leaves and tuber extracts of rat taro are known to contain secondary metabolite compounds belonging to the class of flavonoids, alkaloids, triterpenoids, steroids, saponins, and tannins which act as antimicrobials. This study aims to determine the effectiveness of leaf, stem and tuber extracts of rat taro (Typhonium flagelliforme (Lodd)) as a biofungicide against the cause of leaf fall (Pestalotiopsis sp.) on rubber plants (Hevea brasiliensis). Leaf samples came from rubber plants at PTPN III Karet Sei Putih, Galan District, Deli Serdang Regency, North Sumatra. Pestalotiopsis sp. was isolated from plant parts showing leaf fall symptoms. Pieces of rubber leaves infected with Pestalotiopsis sp. was grown on PDA media in a petri dish and incubated for Â±7 days at room temperature 26â€“28oC. After incubation, microscopic identification of the conidia of the fungus was carried out. In vitro test of the inhibition power of extracts of leaves, stems and tubers of rat taro against the fungus Pestalotiopsis sp. was carried out in a petri dish using the fungus culture method. The results of the phytochemical screening showed that the leaf, stem and tuber extracts of rat taro contained chemical compounds of flavonoids, tannins, saponins, alkoloids, and steroids/triterpenoids. The results showed that the leaves, stems and tuber extracts of rat taro (T. flagelliforme L.) have potential as biofungicides, K13 treatment of tuber extract of rat taro (Typhonium flagelliforme L.) 9% was the best treatment which could inhibit the growth of Pestalotiopsis sp.